2020
DOI: 10.1021/acs.cgd.0c00497
|View full text |Cite
|
Sign up to set email alerts
|

Racemic Conglomerate Formation via Crystallization of Metaxalone from Volatile Deep Eutectic Solvents

Abstract: The pharmaceutical metaxalone (MTX) was obtained as a conglomerate Form A-R/S, via a newly reported crystallization method exploiting volatile deep eutectic solvents.Homochiral crystals of Form A-S, could previously be obtained only by crystallization from enantiopure MTX, synthesized from enantiopure starting materials, and never from a racemic solution of MTX. Homochiral crystals of Form A-R were obtained here concomitantly for the first time. Powder X-ray diffraction and chiral high performance liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Although this assumption might be applicable to many DES, experimental investigations to prove its validity are lacking. It has been shown that polymorphism can be observed in many eutectic systems. Corvis et al reported the formation of a 1:1 molar ratio cocrystal in the lidocaine/ l -menthol binary eutectic system. Recently, Hall et al used synchrotron X-ray powder diffraction (XRD) and DSC to prove the formation of several metastable solid phases in different eutectic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Although this assumption might be applicable to many DES, experimental investigations to prove its validity are lacking. It has been shown that polymorphism can be observed in many eutectic systems. Corvis et al reported the formation of a 1:1 molar ratio cocrystal in the lidocaine/ l -menthol binary eutectic system. Recently, Hall et al used synchrotron X-ray powder diffraction (XRD) and DSC to prove the formation of several metastable solid phases in different eutectic systems.…”
Section: Introductionmentioning
confidence: 99%
“…9 Furthermore, in the phenol : metaxalone VODES system it was shown that the formation of a phenol co-crystal with a ratio of 3 : 1 is a necessary intermediate to the metastable conglomerate form A-R/S. 11 The depression in melting point of a DES compared to the isolated constituents is commonly attributed to charge delocalisation, caused by the formation of a network of hydrogen bonding motifs between the constituent species. 12 However, low-temperature powder X-ray diffraction (pXRD) studies of the choline chloride : urea DES uncovered the formation of a lowmelting co-crystalline phase of the mixture.…”
mentioning
confidence: 99%
“…Moreover, DES are easier and less expensive to prepare compared to IL. Therefore, more attention is directed to their use in several process applications, for example, in liquid–liquid chromatography ( Roehrer et al, 2016 ; Bezold and Minceva, 2019 ; Cai and Qiu, 2019 ), extraction of bioactive compounds ( Kalhor and Ghandi, 2019 ; Makoś et al, 2020 ; Perna et al, 2020 ; Rodríguez-Llorente et al, 2020 ; Fernández et al, 2022 ), and crystallization ( Emami and Shayanfar, 2020 ; Hall et al, 2020 ; Hamilton et al, 2020 ; Potticary et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%